Defisit Operasionalisasi Proporsionalitas dalam Pengamanan VVIP oleh Kepolisian Daerah Pasca UU kepolisian 2026 - Wisnu Pamungkas; Haidan Angga Kusumah (Jurnal Hukum, Administrasi Publik dan Negara, 2026)
VVIP security brings together the state's obligation to protect top officials with restrictions on citizens' rights through road closures, inspections, expulsions, and the use of force. Amendments to the Police Law in 2026 demand a critical re-examination of operational legality and proportionality. This article analyzes the adequacy of the legal basis for VVIP security by the regional police and formulates measurable, proportional, accountable, and human rights-oriented operational standards. The research uses a normative legal design enriched by sociolegal evidence through purposive interviews with the leadership of Dit Samapta, the Head of the VIP Sub-Directorate, the head of the unit, and implementing personnel. The analysis was carried out by vertical synchronization, systematic interpretation, three-stage proportionality test, and triangulation between sources and between levels of positions. The results of the study show that the institutional authority of the National Police is available, but the authority of action has not been translated into special procedures regarding road closures, preventive checks, crowd handling, force escalation, and reporting. Six gaps were identified: authority basis, road procedures, power stages, threat assessment, respect for rights, and accountability. The changes to the law strengthen the principles of proportionality, transparency, and supervision, but have not yet provided a matrix of operational decisions. This article offers a documented proportionality model that links legal mandates, threat levels, least mitigated alternatives, impact balance, and audit footprint as a series of VVIP security decisions of Indonesian regional police.